2022
DOI: 10.1002/solr.202100973
|View full text |Cite
|
Sign up to set email alerts
|

Facet Orientation and Intermediate Phase Regulation via a Green Antisolvent for High‐Performance Perovskite Solar Cells

Abstract: Herein, isobutanol (IBA) as a new type of green antisolvent for improving the performance of perovskite solar cells (PSCs) is demonstrated. Compared to the commonly used chlorobenzene (CB), IBA treatment enables a preferred (111) crystal orientation, better crystallinity, enlarged grain size of the perovskite film, and penetrated grain crystal throughout the film. IBA antisolvent can effectively suppress the formation of δ-phase and favor the formation of α-phase during perovskite film crystallization. The sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…At the same time, a strong peak corresponding to PbI 2 appears at 12.9°, which is consistent with the report mentioned above. [ 43 ] Encouragingly, after adding the BCP and BCP‐3N into the ethanol antisolvent to passivates these Pb(II) defects, the peak intensity of PbI 2 was significantly reduced with BCP as a comparison, suggesting that the stronger coordination ability of BCP‐3N to PbI 2 has effectively restrained its further accumulation. In addition, further analysis of the lattice parameters showed that the half‐peak width of the film treated with BCP‐3N was narrower (Table S3, Supporting Information), indicating the perovskite grain size in the bulk phase was larger, which was confirmed by cross‐sectional scanning electron microscope (SEM) in Figure S6, Supporting Information, as well.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, a strong peak corresponding to PbI 2 appears at 12.9°, which is consistent with the report mentioned above. [ 43 ] Encouragingly, after adding the BCP and BCP‐3N into the ethanol antisolvent to passivates these Pb(II) defects, the peak intensity of PbI 2 was significantly reduced with BCP as a comparison, suggesting that the stronger coordination ability of BCP‐3N to PbI 2 has effectively restrained its further accumulation. In addition, further analysis of the lattice parameters showed that the half‐peak width of the film treated with BCP‐3N was narrower (Table S3, Supporting Information), indicating the perovskite grain size in the bulk phase was larger, which was confirmed by cross‐sectional scanning electron microscope (SEM) in Figure S6, Supporting Information, as well.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other methods such as component engineering, additive engineering, and antisolvent engineering can also be able to regulate the crystal orientation to a certain extent, but it seems difficult to achieve quasi-monocrystalline films with a single dominant orientation. 32,33,43,53 A comparison of various regulation methods and their core factors affecting the facet orientation is shown in Table 1.…”
Section: T H Imentioning
confidence: 99%
“…This work is a breakthrough of the restrictions on the conventional preferential (001) orientation, expanding the breadth of seeding-induced growth on individually tailored dominant facet orientations. In addition, other methods such as component engineering, additive engineering, and antisolvent engineering can also be able to regulate the crystal orientation to a certain extent, but it seems difficult to achieve quasi-monocrystalline films with a single dominant orientation. ,,, A comparison of various regulation methods and their core factors affecting the facet orientation is shown in Table .…”
mentioning
confidence: 99%
“…Wang et al reported that isobutanol cound regulate the mesophase of perovskite and enables (111)‐oriented perovskite film. [ 28 ] However, there is still lack of systematic studies on the relationship between the intermediates, nucleation, and film orientation, especially the nucleation mechanism of perovskite thin films before annealing.…”
Section: Introductionmentioning
confidence: 99%